Governance Practices At Financial Regulatory and Supervisory Agencies - Novoa, Alicia (IMF Working Papers; Working Paper ;, 2009)
This paper summarizes the results of a survey of financial supervisory agencies in IMF member countries conducted in 2007. Responses were received from 140 financial sector supervisors in 103 countries. A majority of these are separate stand-alone agencies, though, a majority of bank supervisors are part of a central bank. The survey asked respondents about their governance structure and practices, as well as practices and policies related to public transparency and accountability. Most agencies reported having operational independence. Bank supervisors were unique in viewing financial stability as part of their mandate.